ANALISIS KETERWAKILAN PEREMPUAN DI DPRD SELUMA : (Studi Implementasi Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilu) - Hasti Marlena; Rekho Adriadi; Titi Darmi (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2019)
This study examines the implementation of Law No. 7 of 2017 concerning elections related to the representation of women in parliament, namely the number of Seluma District DPRDs totaling 30 people and only 4 women elected in parliament. The purpose of this study was to determine the implementation of the Law Number 07 Year 2017 regarding the representation of women in Seluma Regency. According to Law No. 7 of 2017 the requirements include at least 30% quota of women's representation in the nomination of elections for political parties, but in reality in Seluma District it is known that women's representation is still very low from the last few periods.Researchers in this case, see how Law No. 7 of 2017 concerning elections related to women's representation in parliament is implemented throughout, researchers analyze using the theory of Merilee S. Grindle (1890) qualitative descriptive method with data obtained through the technique of "observation observation and documentation The data analysis technique used is the next stage of data collection, the data reduction stage and the data presentation stage, which finally concludes with the data testing technique using triangulation through the presentation of the interviewees by interviewing techniques.From the conclusions of the study it was found that the policy was only a formality requirement so that the Seluma District saw that women's representation was very low and did not meet the 30% quota related to policies that resulted in the benefits of policy implementation